Towards reduction of postharvest losses in mushroom farming in Ghana: Methods and strategies - Gameli, Kokoti Kwabla (Research Journal in Advanced Social Sciences, 2020)
There are about 69,000 known mushroom species of which 2,000 are regarded as edible mushrooms (Chang and Tropics, 1991). Edible mushrooms have been collected and consumed by people for over thousand years ago. Some wild species harvested in Ghana are Termitomyces spp, Volvariella volvacea, Coprinus spp, Cantherellus aurantiacus (Obodai, 2001). Edible mushrooms are good sources of vitamin B2, niacin and foliate, with contents varying in the ranges 1.8 – 5.1, 31 – 65 and 0.30 – 0.64mg/100g dry weight respectively (Mattila et al., 2001). Harvesting is done by twisting the fruiting bodies from the substrate by hand, leaving no bits of stem behind. The survey was conducted between November and December, 2014 to obtain baseline data on farmers’ knowledge on methods of harvesting, postharvest management and ways of reducing postharvest losses of wild mushrooms in the Kpelezo community in the Volta Region of Ghana. Fifty farmers (50) were randomly selected from the community for the survey. From the study, 37% of the farmers suggested that postharvest losses of mushroom can be minimized by digging the soil around the mushrooms before pulling them with hands. 31% of the farmers were of the view that losses can be minimized by handling mushrooms with care and tying them up with threads. 22% of farmers were of the opinion that proper handling of mushrooms after harvesting can reduce losses.